ANALISIS PENERAPAN PROGRAM GREEN SCHOOL DALAM MENANAMKAN NILAI KARAKTER PEDULI LINGKUNGAN PESERTA DIDIK SD INP. TAPPANJENG - Sahabuddin, Erma Suryani; Muhammad Irfan; Nurfajriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to describe the implementation of character education focusing on environmental awareness at SD Inp. Tappanjeng, identify the challenges faced, and explore efforts to overcome these challenges through the application of a green school concept. The research employs a qualitative descriptive method with primary data obtained from interviews with the principal, teachers, and students, as well as secondary data from related documents. Data collection was carried out through observation, interviews, and documentation, with data analysis following the steps of data collection, reduction, presentation, and conclusion drawing. Data validity was tested using source and technique triangulation. The results of the study show that character education on environmental awareness is implemented through curriculum development, integration across all subjects, school culture, learning processes, and school health programs. The main challenges encountered include the low level of environmental awareness among students at home due to a lack of education from parents and insufficient support and practical examples from them. Efforts to address these challenges include routine discussion programs and parental involvement in school activities such as cleanliness competitions, recycling, and tree planting. Collaboration between the school and families has been effective in enhancing students' environmental awareness, emphasizing the importance of synergy between education at school and at home.